The Influence of Social Media Marketing Activity and Electronic Word of Mouth on Lazada E-Commerce Consumer Purchasing Decisions - Iskamto, Dedi; Tory, Fadil Athariq; Afthanorhan, Asyraf (Universitas Negeri Malang, 2025)
In an advancing digital era, information and communication technology has undergone rapid development, affecting various aspects of life, including consumer behavior. Shopping activities that used to be done conventionally are now starting to shift to e-commerce platforms, one of which is Lazada. Lazada, as one of the largest e-commerce platforms in Indonesia, faces challenges to stay relevant and attract consumers in the midst of increasingly fierce competition. This study aims to analyze the effect of marketing activities through social media (Social Media Marketing Activity) and electronic word of mouth communication (Electronic Word of Mouth) on consumer purchasing decisions on the Lazada e-commerce platform. Through a quantitative approach, this study collected data from respondents who are active Lazada users to measure the extent of the influence of these two variables on purchasing decisions. The results showed that both Social Media Marketing Activity and Electronic Word of Mouth have a significant influence on consumer purchasing decisions. This research is expected to provide insights for marketing practitioners in developing effective digital marketing strategies to increase loyalty and sales on e-commerce platforms. Keywords: Electronic Word of Mouth, Lazada, Purchase Decision, Social Media